Perubahan Penggunaan Lahan Di Kecamatan Nanggalo Kota Padang - Arie Zella Putra Ulni; Dasrizal; Elvi Zuriyani; Afrital Rezki; Erna Juita (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Changes in land use are basically unavoidable in the implementation of development. Rapid population growth and the increasing demand for land by the community, often results in conflicts of interest over land use and discrepancies between land use and its allotment plan. The land is limited and cannot be added except by reclamation activities, so that limited land in urban areas causes cities to develop physically towards the outskirts of the city. The increase in the number of urban residents also means an increase in the need for land. Because land cannot increase, what happens is a change in land use which tends to reduce the proportion of land that was previously agricultural land use to non-agricultural land. Changes in land use are all human interventions, both permanently and cyclically, to a collection of natural resources and artificial resources, which as a whole is called land, with the aim of fulfilling their needs, both material and spiritual, or both. Likewise with the land use that occurred in the District of Nanggalo, in 2006 there were still many agricultural lands found.